Pengendalian Biaya dan Waktu dengan Metode Earned Value pada Proyek Pembangunan Hotel Citra Dream Blok III Bintaro Tanggerang Selatan - HP, Lilik Setyawan; Wicaksono, Damar Adjie; Slameto, P Joko; Dimyati, Dimyati; Pramono, Didiek; Susanto, Remigius Hari (Jurnal Kridatama Sains dan Teknologi, 2024)
Delays in project implementation often occur, therefore it is necessary to carry out control on the project so that its implementation can be carried out again according to the time and cost that have been determined. Control was carried out on the Citra Dream Hotel Development Project, Block III Bintaro. The planned implementation time at that stage was 560 days. Acceleration was carried out using the Earned Value method. The yield value method is a control method used to control project costs and schedules. This method provides information on project performance in a reporting period and provides information on the predicted costs required and the time required to complete all work based on performance indicators at the time of reporting. In the Citra Dream Hotel Development Project, Block III Bintaro, the BCWS (Budget Cost of Work Schedule) value was obtained = Rp. 2,517,673,147,940.23, the BCWP (Budget Cost of Work Performance) value = Rp. 2,441,825,773,572.85, the ACWP (Actual Cost of Work Performance) value = Rp. 2,342,994,346,366.87, based on the schedule aspect, this project is delayed, this is proven by the SV (Schedule Variance) value = -Rp. 919,362,113.54 and SPI (Schedule Performance Index) = 0.97 <1. Based on the acceleration management that has been carried out to accelerate the project by adding overtime hours for 2 hours. The addition of overtime hours can save the project duration by up to 9 days